Development and psychometric validation of a shorter version of the Breast Cancer Treatment Outcome Scale (BCTOS-12) - Hennigs, André; Heil, Jörg; Golatta, Michael; Fastner, Sarah; Riedel, Fabian; Rauch, Geraldine; Feißt, Manuel (The breast, 2018)
Objectives: Aesthetic and functional outcomes after oncoplastic breast-conserving surgery (BCS) are directly related to the patients' quality of life (QoL). The Breast Cancer Treatment Outcome Scale (BCTOS) is a validated but burdensome questionnaire for the assessment of these outcomes. The aim of the study was to strengthen and focus the BCTOS instrument by reducing the number of items and subscales without loss of information and validity. Methods: This study used a dataset of 871 patients with stage 0 - III breast cancer, from a prospective cohort study, who underwent BCS. We investigated correlations and other criteria of homogeneity of the BCTOS items to identify redundancies. An exploratory factor analysis was used to remodel the item-factor structure. Correlation and linear regression analysis with validated QoL subscales assessed the convergent and discriminant validity of the modified BCTOS structure. Results: The factor analysis revealed two distinct subscales for aesthetic and functional outcomes. It was possible to reduce the 22 items of the original BCTOS to 12 items, thus the “BCTOS-12”. The two new scales had very good internal consistency: Cronbach's α = 0.86 for the new Aesthetic Status subscale and α = 0.81 for the new Functional Status subscale. Bootstrapping confirmed the item-factor structure for all 10,000 samples, remarkably. Conclusion: The modified BCTOS questionnaire with only 12 items (BCTOS-12) is shorter, easier to interpret, and shows good validity.
Gesehen am 07.05.2018